Serial Neurologic Assessment in Pediatrics (SNAP): A New Tool for Bedside Neurologic Assessment of Critically Ill Children*. Issue 5 (May 2021) - Kirschen, Matthew P.; Smith, Katherine A.; Snyder, Megan; Zhang, Bingqing; Flibotte, John; Heimall, Lauren; Budzynski, Katrina; DeLeo, Ryan; Cona, Jackelyn; Bocage, Claire; Hur, Lynn; Winters, Madeline; et al.
Abstract : OBJECTIVES: We developed a tool, Serial Neurologic Assessment in Pediatrics, to screen for neurologic changes in patients, including those who are intubated, are sedated, and/or have developmental disabilities. Our aims were to: 1) determine protocol adherence when performing Serial Neurologic Assessment in Pediatrics, 2) determine the interrater reliability between nurses, and 3) assess the feasibility and acceptability of using Serial Neurologic Assessment in Pediatrics compared with the Glasgow Coma Scale. DESIGN: Mixed-methods, observational cohort. SETTING: Pediatric and neonatal ICUs. SUBJECTS: Critical care nurses and patients. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Serial Neurologic Assessment in Pediatrics assesses Mental Status, Cranial Nerves, Communication, and Motor Function, with scales for children less than 6 months, greater than or equal to 6 months to less than 2 years, and greater than or equal to 2 years old. We assessed protocol adherence with standardized observations. We assessed the interrater reliability of independent Serial Neurologic Assessment in Pediatrics assessments between pairs of trained nurses by percent- and bias- adjusted kappa and percent agreement. Semistructured interviews with nurses evaluated acceptability and feasibility after nurses used Serial Neurologic Assessment in Pediatrics concurrently with Glasgow Coma Scale during routine care. Ninety-eight percent of nurses (43/44) had 100% protocol adherence on the standardized checklist. Forty-three nurses performed 387 paired Serial Neurologic Assessment in Pediatrics assessments (149 < 6 mo; 91 ≥ 6 mo to < 2 yr, and 147 ≥ 2 yr) on 299 patients. Interrater reliability was substantial to near-perfect across all components for each age-based Serial Neurologic Assessment in Pediatrics scale. Percent agreement was independent of developmental disabilities for all Serial Neurologic Assessment in Pediatrics components except Mental Status and lower extremity Motor Function for patients deemed "Able to Participate" with the assessment. Nurses reported that they felt Serial Neurologic Assessment in Pediatrics, compared with Glasgow Coma Scale, was easier to use and clearer in describing the neurologic status of patients who were intubated, were sedated, and/or had developmental disabilities. About 92% of nurses preferred to use Serial Neurologic Assessment in Pediatrics over Glasgow Coma Scale. CONCLUSIONS: When used by critical care nurses, Serial Neurologic Assessment in Pediatrics has excellent protocol adherence, substantial to near-perfect interrater reliability, and is feasible to implement. Further work will determine the sensitivity and specificity for detecting clinically meaningful neurologic decline. Abstract : Supplemental Digital Content is available in the text.